Three-Dimensional Virtual Reconstruction Method versus Standard Fluoroscopy as a Guiding Tool for an Optimal Puncture Rout in Patients Undergoing Percutaneous Nephrolithotomy: A Randomized Trial Study - Hosseini, Seyed Reza; Tehranipour , Elham; Khadem, Aliakbar; Alwedaie, Sayed Mohammed Jawad (Urology Journal, 2024)
Purpose: Three-Dimensional (3D) could help for planning and creating an optimal access route in percutaneous nephrolithotomy (PCNL) procedure by achieving a more accurate approach to the renal collecting system and stone treatment while decreasing the risk of complications. The aim of our study is to compare the efficacy of 3D imaging technique with standard fluoroscopy method as a guiding tool for renal stone location while striving to reduce intra-operative X-ray exposure in the former method. Materials and Methods: This randomised clinical trial enrolled 48 PCNL candidates who were referred to Sina Hospital (Tehran, Iran). Participants were divided into two equal groups of intervention (3D virtual reconstruction) and control, using block randomization method. Age, sex, stone type and location, X-ray exposure during the procedure, stone access accuracy rate and the necessity of blood transfusion during surgery were taken into account. Results: The Mean age of participants (n = 48) was 46.4 ± 4.8 years, 34 (70.8%) were male, 27 (56.3%) had partial staghorn stones and all participants had stones within the lower calyx. The radiation exposure time, stone access time and stone size were 2.99 ± 1.81 seconds, 272.3 ± 108.9 seconds and 23.06 ± 2.28 mm, respectively. In the intervention group, the accuracy rate for lower calyceal stone access was 91.5%. Also, X-ray exposure and time to stone access were significantly lower in the intervention group compared to the controls (P < 0.001). Conclusion: We concluded that the utilization of 3D technology in the pre-operative location of renal calculi in PCNL candidates may result in a significant improvement in the accuracy and time to access the renal calculi, as well as reduction in X-ray exposure.